In this study: Adapting to the new normal in COVID-19 pandemic; a global survey & literature review. (13th April 2021) - Arain, F.; Tohid, A.; Arain, A.; Adam, D.; Khan, F.; Talpur, A.; Arain, A.; Azeem, W.
Abstract : Introduction: Globally, governments have enforced protective measures of social distancing to prevent COVID-19 spread. The lifestyles of public have essentially transformed due to these actions. This study evaluates the effects of COVID-19 on connections and behavior/life adaptations. Objectives: Changes in life style and behavior in COVID-19-Pandemic Methods: We conducted a global cross-sectional study via survey on phone apps and social media platforms in population aged ≥ 16, including questions regarding demographic data and lifestyle changes. We also searched databases APA PsycNet, PubMed, PsycINFO, and Medline; reviewed 40 articles and included 3 in this review, a cross-sectional online survey 1, a planned questionnaire 2, and a study on 600 adolescents, age 10-19 in Palestine 3 Results: Our survey data showed total of 1002 responses, 31.7% decreased sleep, 42.1% increased appetite, 70.6% bulk-buying, and 50.2% weight gain. 43.1% less socialization than before, 78.7% increased screen time, 53.5% excessive hand washing/wiping surfaces, 45% reported social distancing facilitated in overpowering the fear of contracting infection, 29.4% negative impact on relationships, 80.7% noticed changes in behavior including shaking hands/hugging/speaking with a mask on, 49.5% adopted new hobbies, 34.9% showed increase in meditation. The literature review revealed that since COVID-19, there is an increase in screen time, weight, appetite, sleep, and a decrease in physical activity 1-3, and greater adherence to the Mediterranean diet in younger population 2 Conclusions: COVID-19 induced quarantine has caused increased screen time, appetite, weight gain, adoption of new hobbies, bulk-buying, hand washing, meditation, reduced sleep, and negatively impacted interaction/relationships. COVID-19 pandemic is ongoing and our data needs further assessment in more population studies. Disclosure: No significant relationships.